MODERN METHODS, MODELS AND SOFTWARE TOOLS FOR IMPLEMENTATION AND OPTIMIZATION OF IOT SYSTEMS (INTERNET OF THINGS) - Khomenko, Yevheniy (Journal of Information Technologies in Education (ITE), 2024)
This article presents an analysis of modern methods, models, and tools used to create and optimize Internet of Things (IoT) systems. It examines in detail the variety of approaches and software solutions, reflecting the dynamic growth in the field of automation, which is being actively developed by both leading international IT companies such as Google, Apple and Xiaomi, and domestic firms, in particular AJAX, which are gaining popularity in the market. The article highlights the importance of IoT in various aspects of modern life, including energy efficiency, security, and business process optimization. The author focuses on the continuous development of technologies that open up new opportunities for users and improve their quality of life. The author also considers the integration of IoT into various fields of activity, which can lead to a significant positive impact on society and the economy. In addition, the article provides an overview of the history of the Internet of Things, presenting the evolution and key milestones in this area. Modern communication technologies that are the basis for IoT devices are also considered. The author identifies the basic criteria that modern reliable systems must meet, analyzing them in terms of efficiency, scalability, and security. The article also contains an analysis of several popular off-the-shelf system solutions on the market. Each of them is characterized by characteristics, advantages, disadvantages, and unique features. This provides a deeper understanding of the variety of options available and helps in choosing the right system for their individual needs and budget. The article is a useful resource for those looking for updated and comprehensive information on modern IoT systems and their implementation.